Ix2+2I=7
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) đặc : \(x=a+bi\) với \(a;b\in R\) và \(i^2=-1\)
ta có : \(\left(1+2i\right)x-4\left(4-5i\right)=-7+3i\)
\(\Leftrightarrow\left(1+2i\right)\left(a+bi\right)-4\left(4-5i\right)=-7+3i\)
\(\Leftrightarrow a-2b+2ai+bi-16+20i=-7+3i\)
\(\Leftrightarrow\left(a-2b-16\right)+\left(2a+b+20\right)i=-7+3i\)
\(\Leftrightarrow\left\{{}\begin{matrix}a-2b-16=-7\\2a+b+20=3\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}a-2b=9\\2a+b=-17\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}a=-5\\b=-7\end{matrix}\right.\) vậy \(x=-5-7i\)
câu b lm tương tự nha .
Xét x<-2=>x+2<0=>Ix+2I=-x-2
=>3x+6<3.(-2)+6=>3x+6<0=>I3x+6I=-3x-6
=>I3x+6I-Ix+2I=7
=>-3x-6+x+2=7
=>(-3x+x)-(6-2)=7
=>-2x-4=7
=>-2x=7+4
=>-2x=11
=>x=11:(-2)
=>x=-11/2
Xét x>_-2=>x+2>_0=>Ix+2I=x+2
=>3x+6>_3.(-2)+6=>3x+6>_0=>I3x+6I=3x+6
=>I3x+6I-Ix+2I=7
=>3x+6+x+2=7
=>(3x+x)+(6+2)=7
=>4x+8=7
=>4x=7-8
=>4x=-1
=>x=-1/4
Vậy x=-11/2,-1/4
(3 - 2i)z + (4 + 5i) = 7 + 3i
⇔ (3 – 2i).z = (7 + 3i) – (4 + 5i)
⇔ (3 – 2i).z = 3 – 2i
⇔ z = 1.
-9/2 va 5/2
\(-\frac{9}{2}\) và\(\frac{5}{2}\)